The Ozolian Locris in Roman Times: A Lost People in a Fragmented Land - Zachos, George (Tekmeria, 2023)
Pausanias, arriving at Amphissa shortly after AD 170, met with Aitolian residents -instead of Locrians- who wanted to renounce the Locrian past of the city. These Aitolians, according to him, had refused to move to Patras or Nicopolis, when Augustus divided Aitolia between the two new colonies. Pausanias also visited Myania, Chaleion and Naupactos and mentions that the rest of the Ozolian Locris, except Amphissa, was “under the control” of the Greeks of Patras. The combination of the ancient sources (Pausanias, Strabo, Pliny and the epigraphic record of West Locris) with the archaeological finds from the region provides some information on the status of the Ozolian cities in the Roman period. The new status quo imposed by Rome in Aitolia and in Epictetos Aitolia fragmented the Hesperians and strongly affected the settlement pattern of the region. As far as Amphissa is concerned, an honorary inscription from the sanctuary of Athena Kranaia in Elateia may shed light on the matter of its new Aitolian population.